Orthodontist's Role in Orthognathic Surgery - Wirthlin, John O.; Shetye, Pradip R. (Seminars in Plastic Surgery, 2013)
Orthognathic surgery can eliminate severe esthetic and functional deformities and be a life-changing event for a patient. An orthodontist's role in orthognathic surgery can be divided into several phases: the initial evaluation, presurgical orthodontics, surgical planning, and postsurgical orthodontics. At each of these phases, collaboration between the orthodontist and the surgeon is critical. The ability of an orthodontist and a surgeon to coordinate their efforts during this time is what will lead to a successful outcome.
Keywords: orthodontist; orthognathic surgery; collaboration